Pengaruh Kinerja Pegawai Terhadap Kualitas Pelayanan Publik di Kecamatan Astanaanyar - Tri Lestari, Anisa; Wilma Zuarko Adji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Success in the organization is inseparable from the performance of its employees in serving, so that it can meet the expectations of society with satisfying service quality. This study aims to determine how much influence the variable employee performance has on the variable quality of public services in Astanaanyar District. This research method uses a type of quantitative research, using a questionnaire data collection method. The population in this study were Astanaanyar District employees and the community who received services with a total of 60 people. Data processing in this study was assisted by SPSS software version 23.00. the results of data analysis were obtained from the results of the Validity Test, Reliability Test, Normality Test, Heteroscedasticity Test, F Test, T Test and the Coefficient of Determination. Based on the results of the F test and T test, the results of data analysis show that employee performance variables affect service quality variables, and employee performance variables on service quality variables have a positive influence value. As well as the results of the Coefficient of Determination Test explaining that the employee performance variable has an effect on the service quality variable of 37.3%.